Verifying online signatures through an iterative device independent model - Tahsin, Samiha; Molla, Robin; Jamal, Omran (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.